REGULASI HAM DI INDONESIA - Ahmada Ardani Astania Magenda Mirzakhul (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
This paper aims to describe some of the opportunities and challenges methodologically for the idea of formulating a framework for analyzing human rights regulation and implementation of human rights. For this reason, this paper will be divided into three main sections, namely: first, regarding the discussion of human rights enforcement in Indonesia; second, discussing human rights that have not been regulated in the 1945 Constitution; finally, the implementation of human rights in Indonesia.